Analisis Metode Economic Order Quanity Guna Melakukan Efisiensi Persediaan Bahan Baku dan Efisiensi Biaya di Industri Bakery - Spalanzani, Widya; Sarengat, Panji; Rosihan, Rifda Ilahy; Tambunan, Erwin Barita Maniur (Politeknik ATI Padang, 2023)
One of the companies in East Bekasi is a company engaged in the bread industry, with the product being sandwiches. The purpose of this research is to perform raw material efficiency and cost savings of raw material inventory. In this study, identified the bread production process for 1 period (3 months). It is known that this company ordered raw materials, namely 2100 kg of flour and 480 kg of granulated sugar. However, in reality, only 1537 kg of wheat flour was used and 379 kg of granulated sugar. There is a difference between ordering raw materials and using raw materials so that the costs incurred in carrying out raw material inventory exceed the limits of the costs that have been determined by the company. The method used is the Economic Order Quantity (EOQ) method. The goal is to control the number of raw material orders made by this company and indirectly to save raw material inventory costs. The findings are comparing calculations by companies using EOQ, the efficiency of raw materials after using the EOQ method for wheat flour is 542 kg and granulated sugar is 93 kg and savings in raw material inventory costs for wheat flour is Rp. 156,437 and granulated sugar is Rp. 212,092